212k views
2 votes
Select the correct locations on the image.

Select function f and function g such that the sum of f and g is function h.

Select the correct locations on the image. Select function f and function g such that-example-1
User ZijunLost
by
6.0k points

2 Answers

5 votes

Answer:

f(x) = -2x + 3

g(x) = 7x - 9

f(x) + g(x) = -2x +3 + 7x - 9

f(x) + g(x) = 5x -6 = h(x)

Explanation:

User Sam De Meyer
by
6.1k points
7 votes
This has to be done by hit and trial method. i.e. you have to checking adding which of the function from first column to function in second column will yield h(x).

The following functions yield given value of h(x).

f(x) = -2x + 3
g(x) = 7x - 9

f(x) + g(x) = -2x +3 + 7x - 9
f(x) + g(x) = 5x -6 = h(x)

So, from 1st column its the cell number 3, and from the second column its the cell number 2.
User Mouffette
by
5.9k points